Kultura jako podstawa potencjału motywacyjnego w polityce zagranicznej Republiki Federalnej Niemiec - Kohtamäki, Natalia (Polski Przegląd Stosunków Międzynarodowych, 2018)
Culture as an Element of the Motivational Power in the Foreign Policy of the Federal Republic of Germany The potential of the state may usually be measured by comparing its power with those of other countries. The term ‘power’ means the state's ability to mobilize and use all available resources - material, social, cultural - to fulfill its needs, goals and interests in an international environment. Power is an element used in the foreign policy of each state which is difficult to measure, examine or compare. The difficulty stems from the complexity of the phenomenon which consists of material elements – such as territory, population, or economy – but also of motivational factors. Those elements are culturally and ideologically conditioned, and cover subjective and psychological aspects which makes them difficult to define. The aim of the paper is to show the building process of the motivational potential by using the German example. In this context it is especially important to explain the main mechanisms and instruments of German public diplomacy which in this text has the same meaning as ‘foreign cultural policy’. After the Second World War the Federal Republic of Germany developed a new strategy for its presence in the international arena. After the war German politicians understood how important cultural influences can be in the developing of the new German image. In the 1970´s this knowledge found a concrete shape in the government and parliament documents, in which the need for a multicultural dialog and understanding of partners was especially accented. From this perspective Germany saw the culture as the third main pillar of its foreign policy, alongside to the politic and economic aspects. After more than 40 years of German cultural foreign policy its instruments are still playing a very important role in the shaping of German position in the world and can be seen as a model for other countries.